Comparisons between transparency in the United States of America(US) corporate bond market and European corporate bond market: Criticisms of transparency in US markets from European markets perspective - Zainudin W.N.R.A.; Board J. (International Business Information Management Association, IBIMA, 2024)
Indexed by WOS/ Scopus